206k views
0 votes
-4y+7x=49 -16y+9x=63

2 Answers

6 votes
Here you go!! Hope this helps
-4y+7x=49 -16y+9x=63-example-1
User Niklas Heidloff
by
4.9k points
6 votes

Answer:

x = 7,

y = 0

Explanation:

-4y + 7x = 49

-16y + 9x = 63

multiply the first equation with -4

16y - 28x = -196 now add it to the second equation

-16 y + 9x = 63 (16y will eliminate -16y)

-19x = -133

x = 7

to find y use the value of x in the first or second equation

-4y + 7×7 = 49

y = 0

User PandaWood
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.